A dosimetric comparative analysis of Brainlab elements and Eclipse RapidArc for spine SBRT treatment planning. (1st March 2022) - Deshazer, Garron; Narayanasamy, Ganesh; Bimali, Milan; Galhardo, Edvaldo; Kalantari, Faraz; Xia, Fen; Peñagarícano, Jose; Morrill, Steven
Abstract: Purpose . This is a dosimetric study comparing stereotactic body radiotherapy (SBRT) plans of spine tumors using Brainlab Elements Spine planning module against Eclipse RapidArc plans. Dose conformity, dose gradient, dose fall-off, and patient-specific quality assurance (QA) metrics were evaluated. Methods:Twenty patients were immobilized in supine position using half Vac-Lok. A prescription dose of 16 Gy in a single fraction was planned for Varian TrueBeam. Conformal arc plans were generated with Pencil beam (PB), MonteCarlo (MC) in Elements, and RapidArc with Acuros XB algorithm in Eclipse using identical treatment geometry. Result s. Eclipse, Elements PB, and Elements MC generated dosimetrically conformal plans having Inverse Paddick Conformity Index (IPCI) <1.3. All plans satisfied the dose constraints to target and OARs. Elements PB had a sharper gradient than Elements MC with average GI of 3.67(95% CI: 3.52–3.82) and 4.06 (95% CI: 3.93–4.20) respectively. Eclipse plans were more homogeneous with mean HI = 1.22 (95% CI: 1.20–1.23) that is lower than others. Average maximum clinical target volume (CTV) doses were higher in Elements MC with 22.31 Gy (95% CI: 21.87–22.74), while PB plans have 21.15 Gy (95% CI: 20.36–21.96), respectively. Elements MC and PB plans had lower average dose to 0.35 c.c. of spinal cord (D0.35cc) of 7.60 Gy (95% CI: 7.18–8.02) and 8.42 Gy (95% CI: 7.83–9.01). All plans had >95% points passing the gamma QA criteria at 3%/2 mm. Conclusion . All treatment plans achieved clinically acceptable target coverage >95% and meet spinal cord dose limits. Smart optimization in Brainlab Elements spine module produced dosimetrically superior plans by better spinal cord sparing.